Effect of muscle, ageing time and modified atmosphere packaging conditions on the colour, oxidative and microbiological stability of packed beef. (15th November 2013) - Owczarek‐Fendor, Agnieszka; Vermeulen, An; Van Bree, Ilse; Eriksson, Markus; Lescouhier, Stefaan; De Smet, Stefaan; De Meulenaer, Bruno; Devlieghere, Frank
Summary The objective of this study was to evaluate the influence of two different vacuum ageing times (7 and 14 days) and the impact of the modified atmosphere packaging (MAP) configuration (gas/product ratios: 0.5 and 1 and gas composition: 70% O2 + 30% CO2 and 40% O2 + 30% CO2 + 30% N2) on the quality of fresh beef during subsequent storage at 4 °C. For this purpose, three separate experiments were performed. For each experiment, two different muscles (Longissimus dorsi and Biceps femoris) were sampled from four double‐muscled Belgian Blue beef carcasses. Next to colour, also the evolution in microbial load, pH, O2 and CO2 in the headspace and lipid oxidation at the meat surface were evaluated. A vacuum ageing for 14 days compared with 7 days resulted in a higher initial microbial load on the day of MAP packaging, which resulted finally in a significantly shorter shelf life. This ageing effect was less pronounced on the colour stability and lipid oxidation of the meat samples. No significant influence of the packaging configuration on any of the analysed parameters (colour, microbial load, pH and lipid oxidation at the meat surface) was observed.